Novos ligantes e compostos de coordenação supramoleculares derivados dos ligantes fenilenobis(oxamato) : sintese, análise estrutural e estudos magnéticos - Tamyris Teixeira da Cunha (2015)
In this work were described the synthesis and structural characterization of six new compounds, being three of them ligands with thiooxamate bridges and three supramolecular coordination compounds derived from supramolecular building block [Cu(opba)]2 (opba = 1,2-phenylenebis(oxamate)). The ligands were synthesized by using thionation reaction and Lawesson reagent as the thionation agent, to transform oxamate bridges into thiooxamate. However, the thionation reaction occurred only in the amide group of the starting oxamategroup, and this fact was evidenced by means of single crystal X-ray diffraction. The supramolecular coordination compounds had the metathesis reaction as a synthesis strategy, wherein the building block [Cu(opba)]2- with different starting countercations was submittedto metathesis reaction with the organic salt (p-edap)C12.2H20 (p-edap = 1,1'-etilenebis(4-aminopyridinium)). The influence of the starting counterion was verified by means of structuralelucidationof threedifferentmolecular architectures of the type (p-edap)x[Cu(opba)]v,through single crystal X-ray diffraction analysis. The compounds(10-edap)2[Cu(opba)]2.4H20 and Na2(p-edap)[Cu(opba)]2.6H20 presented dimerization of anionic complex, leading to the formation of dinuclear [Cu(opba)]24- in which copper atoms are connectedbycarboxylatebridges.ThethirdcoordinationcompoundK2(p-edap)[Cu(opba)]2.5H20 do not present dimerization in its structure, leading to believe that potassium atom acts as a counterion and as a spacer in the structure as well, preventing the dimerization. Coordination compounds had their magnetic properties studied and all exhibited antiferromagnetic behavior at lower temperatures. The values of coupling constants (1) for these compounds were determined by least-square fits of the magnetic data, being equalto-1.634(9)cm-'for(p-edap)2[Cu(opba)]2.4H20,-2.291(2)cm-'for Na2(p-edap)[Cu(opba)12.6H20 and -1.652(3) cm-' for K2(p-edap)[Cu(opba)]2.5H20. The saturation of magnetization at 2 K was not reached to the maximum applied field of 50 kOe in all three compounds.